Numerical estimation of the volume of coconut pulp (Cocos nucifera) applying the Montecarlo method - Estela Urbina, Ronald Omar (2021)
This research was developed within the framework of non-face-to-face education due to the sanitary conditions that currently exist due to COVID-19 at the “Fabiola Salazar Leguía” National Intercultural University of Bagua, in the professional career of Civil Engineering, whose syllabic structure The course of Numerical Methods allows to develop experimental activities related to numerical and graphic simulation. This experience arises from the need to establish significant learning, the objective pursued by this investigation is to apply the Monte Carlo method to solve a specific geometry problem that consists of determining the volume of coconut pulp, highlighting that in the province of Bagua and Coconut is produced significantly in neighboring areas, and it is necessary to know its volume for the purposes of marketing its pulp and subsequent extraction of oils. The proposed algorithm would allow to estimate very closely the volume of the pulp of a coconut without having to section it, through this method a margin of percentage error is established on average below 9% of the real volume measured with respect to the result of the simulation in the Basic programming language. The Monte Carlo method used as a teaching strategy is very useful as it fosters meaningful learning in a playful environment, as well as the use of materials from its community.